Features of Anxiety-Depressive Disorders in Individuals of Involutional Age under Current Conditions - Dzeruzhynska, Наталія; Kosova, Олена (Psychosomatic Medicine and General Practice, 2025)
Relevance. Anxiety-depressive disorders (ADD) in individuals of involutional age are a widespread psycho-emotional issue, exacerbated by modern social challenges such as war, economic instability, and age-related crises. According to WHO estimates, about 10 million residents of Ukraine either already suffer from mental disorders or are at increased risk of developing them. Among them, 3.9 million people experience moderate to severe symptoms. The deterioration in quality of life, reduced adaptive capacity, and risk of suicidal behavior require a comprehensive approach to patient assessment and the implementation of effective rehabilitation programs. Aim. Develop a psychorehabilitation algorithm to improve the overall condition and quality of life of involutional-age patients with anxiety-depressive disorders through a comprehensive investigation of the influence of social distress, quality of life, coping strategies, and suicide risk. Objectives. To examine the levels of anxiety, depression, quality of life, coping strategies, and suicide risk in individuals of involutional age with anxiety-depressive disorders, and to develop a psychorehabilitation algorithm based on identified interrelationships. Methods. The study involved 32 patients aged 50–75 years. The Hospital Anxiety and Depression Scale (HADS), Lazarus and Folkman’s Coping Strategies Questionnaire, Quality of life assessment scale (Chaban O.S.), and the Columbia-Suicide Severity Rating Scale (C-SSRS) were used. Pearson correlation analysis was applied to identify relationships between variables. Results and Discussion. The study explored the structure, psychological characteristics, and quality of life in individuals of involutional age with anxiety-depressive disorders under current conditions. A predominance of the anxiety component was observed in the clinical structure of the disorder. Emotion-focused coping strategies (escape-avoidance and distancing) were the most common and showed a moderate positive correlation with suicide risk. Most patients had moderate or low levels of quality of life, which significantly depended on the severity of anxiety, depression, and the nature of coping behavior. A rehabilitation algorithm was developed that includes pharmacological and psychotherapeutic correction, formation of adaptive coping strategies, and social support. The proposed approach contributes to improving the psycho-emotional state and quality of life of involutional-age patients with anxiety-depressive disorders. Conclusions. The proposed psychorehabilitation algorithm enhances the adaptive capacity and quality of life of involutional-age individuals with anxiety-depressive disorders. A promising direction for future research is the development and implementation of long-term individualized psychorehabilitation programs aimed at reducing anxiety, depressive symptoms, and suicidal risk.